A scalable and efficient user authentication scheme for cloud computing environments - Moghaddam F.F.; Moghaddam S.G.; Rouzbeh S.; Araghi S.K.; Alibeigi N.M.; Varnosfaderani S.D. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cloud computing is an emerging technology that is still unclear to many security problems and user authentication, access control, and ensuring the security of stored data in cloud servers are the most challenging issues in cloud-based environment. Accordingly, this paper offers an efficient and scalable user authentication scheme for cloud computing environment. It the suggested model, various tools and techniques have been introduced and used by using the concept of agent. Therefore, a client-based user authentication agent has been introduced to confirm identity of the user in client-side. Furthermore, a cloud-based software-as-a-service application has been used to confirm the process of authentication for unregistered devices. Moreover, there are two separate servers for storing authentication and cryptography resources from main servers to decrease the dependency of user authentication and encryption processes from main server. Cryptography agent was also introduced to encrypt resources before storing on cloud servers. In overall, the theoretical analysis of the suggested scheme shows that, designing this user authentication and access control model will enhance the reliability and rate of trust in cloud computing environments as an emerging and powerful technology in various industries. © 2014 IEEE.